Design of a Full‐Consensus Glutamate Decarboxylase and Its Application to GABA Biosynthesis. (27th October 2021) - Takagi, Hiroshi; Kozuka, Kohei; Mimura, Kenta; Nakano, Shogo; Ito, Sohei
Abstract: Glutamate decarboxylase (GAD) catalyses the decarboxylation of L‐glutamate to gamma‐aminobutyric acid (GABA). Improvement of the enzymatic properties of GAD is important for the low‐cost synthesis of GABA. In this study, utilizing sequences of enzymes homologous with GAD from lactic acid bacteria, highly mutated GADs were designed using sequence‐based protein design methods. Two mutated GADs, FcGAD and AncGAD, generated by full‐consensus design and ancestral sequence reconstruction, had more desirable properties than native GADs. With respect to thermal stability, the half‐life of the designed GADs was about 10 °C higher than that of native GAD. The productivity of FcGAD was considerably higher than those of known GADs; more than 250 mg/L of purified enzyme could be produced in the E. coli expression system. In a production test using 26.4 g of l ‐glutamate and 3.0 g of resting cells, 17.2 g of GABA could be prepared within one hour, without purification, in a one‐pot synthesis. Abstract : Sequence‐based protein design has the potential to generate highly functional enzymes. A full consensus glutamate decarboxylase, FcGAD, has high thermal stability and catalytic rate, which can be used in the synthesis of gamma‐aminobutyric acid (GABA). Utilizing E. coli which express FcGAD as biocatalyst, we achieved the synthesis of GABA at gram scale in a one‐pot reaction.